2016
DOI: 10.1039/c6ra22483k
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and failure mechanisms of nanoscale cellular structures of metallic glasses

Abstract: Cellular metallic glasses (MGs) can be good candidates for structural and functional applications due to their light weight, enhanced ductility and excellent energy absorption performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Understanding the relationship between local atomic structures and mechanical behaviors in metallic glasses (MGs) is of vital importance for current applications and emerging technologies. [1][2][3][4][5][6] There is increasing evidence to suggest that the deformation behavior of MGs is driven by the cooperative organization of irreversible rearrangements of small dynamical clusters, which are triggered by the nonlocal redistribution of elastic stress. [7][8][9] The sequence of such plastic events can contribute to an avalanche process characterized by a power-law scaling of the average stress or energy drop with system size.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between local atomic structures and mechanical behaviors in metallic glasses (MGs) is of vital importance for current applications and emerging technologies. [1][2][3][4][5][6] There is increasing evidence to suggest that the deformation behavior of MGs is driven by the cooperative organization of irreversible rearrangements of small dynamical clusters, which are triggered by the nonlocal redistribution of elastic stress. [7][8][9] The sequence of such plastic events can contribute to an avalanche process characterized by a power-law scaling of the average stress or energy drop with system size.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, atomistic simulations revealed that both the yield and flow stresses of metallic glasses [5] and nanocrystalline metals [6] are higher in compression than in tension. More recently, it was shown that several factors affect deformation and failure of cellular metallic glasses under compression; namely, the cell size controls the transition from localized to homogeneous plastic deformation, while the cell shape, e.g., circular versus hexagonal, might change the strength and energy absorption capacity due to variation in stress concentration at the cell surface [7]. Nevertheless, a complete understanding of the elastic response and yield in homogeneous and porous metallic glasses is yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%